Translation and validation of the Brief Version of the Questionnaire of Olfactory Disorders-Negative Statements to Portuguese - Teixeira-Marques,Francisco (2023)
Abstract Purpose: Olfactory dysfunction can lead to anxiety and depressive symptoms. Given the growth in awareness around olfactory dysfunction since the COVID-19 pandemic, there is a need for standardized questionnaires to allow comparison between series and to better understand and deal with our patients’ struggles. Materials and Methods: Translation and validation of the brief version of the Questionnaire of Olfactory Disorders-Negative Statements (bvQOD-NS) to the Portuguese language. Results: Thirty patients with confirmed olfactory dysfunction by psychophysical olfactory tests met the inclusion criteria. Internal consistency of the bvQOD-NS measured with Cronbach α was 0.589. The intraclass correlation coefficient was 0.925 (confidence interval [CI] 95%: 0.841-0.964), which is indicative of excellent test-retest reproducibility. Conclusions: Portuguese is the seventh most-spoken first language in the world. The Portuguese version of the bvQOD-NS rapid and valid method to better understand our patients’ struggles, ultimately benefiting them and providing important information for the medical community.